Stabilisasi Tanah Lempung Dengan Semen Dan Pasir Laut - M. Gumilar; Eka Apriansyah (JURNAL ILMIAH BERING'S, 2016)
Based on the times the need for careful consideration of the environment around us. Both in the review in terms of economy, industry, agriculture, social, cultural and defense security to be leveling development outcomes will be achieved. Factors supporting these areas is the availability of an adequate road traffic in order to smooth transportation of goods and people. On the other hand to meet the needs of road infrastructure should be review or analysis back when confronted with clay soil stabilization conditions is low, so the cost of which is issued for road maintenance will be higher. Therefore in need through quality improvement efforts penghemetan Yanah on its use for road construction, especially road base by way of mixing the soil with cement and sand. research that we have done with mnggunakan addition of cement and sand and the sea, with a cement content of 8%, 10%, 12%, 14%, and 16% can result in the addition of as much as 14% cement content is the addition that produces the best quality.